Leadership Strategies for Women Lessons from Four Queens on Leadership and Career Development - Vanderbroeck, Paul.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2014)
How do women leaders make it to the top of an organization? How can women stay at the top when most of their colleagues are men? What should women do to exercise leadership well? This book tells the stories of four powerful women who knew the answers to these three questions. Therefore, this book also explicitly identifies the key factors in these leaders$1 (Bcareer success, and it elucidates the competencies that enabled the women to exercise leadership effectively. The four success stories offer women who already serve in leadership roles and those who aspire to become great leaders both inspiration and practical lessons that can be applied to real-world challenges.s
Introduction -- I Cleopatra VII: Leveraging Difference -- II Isabella of Spain: A woman With Visions -- III Elizabeth I of England: Managing a Team of Men -- IV Catherine the Great: Leading Strategic Growth -- V Four Queens: Lessons in Career Development -- VI Four Queens: Lessons in Leadership.
Keywords: Economics; Industrial management; Economics/Management Science; Management/Business for Professionals; Business Strategy/Leadership.; Human Resource Management